Types of sedation used in pediatric dentistry - Aljohani, Hanan Raja; Albalawi, Rinad Abdulmonam; Orri, Fajr Adel; Alshammari, Khalid Mubarak; Shikdar, Narmeen Abdulmannan; Sayhab, Bader Hussain Al; Alkahtani, Hifa Mohammed; Alwably, Alanoud Ali; Algazlan, Alanoud Mohammed; Alghamdi, Ali Abdullah; Alqahtani, Albandari Menahi (International Journal Of Community Medicine And Public Health, 2021)
Childhood dental anxiety usually results from painful and frightening dental traumas. Accordingly, children might want to avoid dental treatment if not adequate precautions were not taken during these settings. Thus, sedation is being widely used in different dental settings with favorable outcomes. In the present literature review, we have discussed sedation’s different types and approaches in pediatric dentistry settings. We also reviewed the main medications that can be administered in these settings, together with the potential routes of administration, safety and contraindications. As a result, the pediatric dentist should identify patients suitable for sedation, choose the right type of sedation, prepare the media for successful procedures, and select the proper medication. Careful monitoring and adequate preparation are also critical to enhance the prognosis and manage the potential complications. Eventually, sedation might improve the compliance of pediatric patients and reduce the dilemma of fear from painful dental procedures. This has been associated with favorable outcomes for the dentist, as well. Therefore, further research is needed for additional validation and innovation in this field.